A photopharmocology study with photoswitchable acetylcholinesterase inhibitors - Dhanaram Tangamanni (2018)
Acetylcholine (ACh) is a crucial neurotransmitter that mediate communication in humans. It modulates cellular excitability by stimulating nicotinic and muscarinic acetylcholine receptors. It is breakdown by acetylcholinesterase (AChE) enzymes into acetate and choline. This leads to a low level of ACh increasing the chances of illness such as Alzheimer’s disease, myasthenia gravis and glaucoma. Hence, studies on AChE inhibitors has been trending for years. Considering the setback of excessive AChE inhibitors which lethal, a dual binding site inhibitor with reversible function is required. Tapping on to photopharmacology will enable us to achieve this function. Light can be applied with high temporal and spatial control as it is noninvasive. By incorporating a photoswitch within the AChE inhibitor it will enable reversible affinity under switchable light irradiation. Herein, we describe the design and synthesis of a novel small molecule photoswitch-inhibitor for reversible AChE functions under switchable light irradiation.